Evaluasi Program Pendidikan Inklusif pada Sekolah Dasar di Lingkup Dinas Pendidikan Kota Mataram Tahun 2020/2021 - Sahat T. Simorangkir (Journal of Instructional Development Research, 2023)
This study was conducted to evaluate and analyze inclusion education programs in elementary schools in Mataram City. This study focuses on: 1). The purpose, goals, and needs of the community towards inclusive education, 2). Plans and strategies for inclusive education programs which include; Human resources, curriculum, and facilities at the Provincial Education Office, 3). program implementation; capacity building, technical assistance and program monitoring and 4) Inclusive school performance outcomes. This study used a mixed method; quantitative and qualitative approach. Quantitative data were collected through simple and qualitative questionnaires through FGDs, in-depth interviews, and observations. The data was analyzed using the CIPP approach to summarize and determine recommendations. Program evaluation criteria are divided into 4 criteria, namely: 1). Context, consisting of community goals and needs for inclusive education programs, 2). Input; plans and strategies of human resources, curriculum and school facilities,3). Process; implementation of capacity building, technical assistance, and monitoring, 4). External; school performance.